Semiarid geomorphology: A methodological proposal for cartographic representation and interpretation of landforms on a detailed scale - Lima, Kleber Carvalho; Lupinacci, Cenira Maria [UNESP] (Revista Brasileira de Geomorfologia, 2021)
The geomorphological cartography at a scale of detail in the Brazilian semiarid presents several aspects to be considered, in order to consistently subsidize geomorphological research in local contexts. In this paper, we aim to present a methodological proposal for detailed geomorphological mapping in crystalline sectors of the Sertaneja Depression (Brazilian semi-arid), developed through a case study. The methodological procedures involved the preparation of the database, analysis of pre-existing geomorphological mapping manuals, fieldwork, elaboration of the geomorphological interpretation key, and the graphic representation of the landforms. In this way, morphographic and morphometric attributes were represented, as well as hydrography, topography, anthropogenic landforms, lithology, chronology, and structural elements. The geomorphological mapping contributed to the understanding of the spatial organization of landforms in the study areas, in addition to contributing to the interpretation of geomorphological facts. Thus, we believe that technical procedures can be used in similar areas or even adapted to different contexts in the semiarid itself.
Geomorfologia do semiárido: proposta metodológica de representação cartográfica e interpretação do relevo em escala de detalhe
Keywords: Geomorphological mapping; Sertaneja Depression; Thematic cartography